Health literacy and the perception of risk in a breast cancer family history clinic. Issue 2 (April 2018) - Rutherford, E.J.; Kelly, J.; Lehane, E.A.; Livingstone, V.; Cotter, B.; Butt, A.; O'Sullivan, M.J.; O Connell, F.; Redmond, H.P.; Corrigan, M.A.
Abstract: Background: Informed consent is an essential component of medical practice, and especially so in procedural based specialties which entail varying degrees of risk. Breast cancer is one of the most common cancers in women, and as such is the focus of extensive research and significant media attention. Despite this, considerable misperception exists regarding the risk of developing breast cancer. Aims: This study aims to examine the accuracy of risk perception of women attending a breast cancer family history clinic, and to explore the relationship between risk perception accuracy and health literacy. Methods: A cross-sectional study of women attending a breast cancer family history clinic (n = 86) was carried out, consisting of a patient survey and a validated health literacy assessment. Patients' perception of personal and population breast cancer risk was compared to actual risk as calculated by a validated risk assessment tool. Results: Significant discordance between real and perceived risks was observed. The majority (83.7%) of women overestimated their personal lifetime risk of developing breast cancer, as well as that of other women of the same age (89.5%). Health literacy was considered potentially inadequate in 37.2% of patients; there was a correlation between low health literacy and increased risk perception inaccuracy across both personal ten-year (rs = 0.224, p = 0.039) and general ten-year population estimations. (rs = 0.267, p = 0.013). Conclusion: Inaccuracy in risk perception is highly prevalent in women attending a breast cancer family history clinic. Health literacy inadequacy is significantly associated with this inaccuracy.